Prebiotic Effect of Lycopene and Dark Chocolate on Gut Microbiome with Systemic Changes in Liver Metabolism, Skeletal Muscles and Skin in Moderately Obese Persons - Wiese, Maria (Biomed Res Int, 2019)
Lycopene rich food and dark chocolate are among the best-documented products with a broad health benefit. This study explored the systemic effect of lycopene and dark chocolate (DC) on gut microbiota, blood, liver metabolism, skeletal muscle tissue oxygenation and skin. 30 volunteers were recruited for this trial, 15 women and 15 men with a mean age of 55 ± 5.7 years and with moderate obesity, 30 < BMI < 35 kg/m(2). They were randomized and divided into five equal interventional groups: three received different formulations of lycopene, one of them with a 7 mg daily dose and two with 30 mg; another group was given 10 g of DC with 7 mg lycopene embedded into its matrix, and the last group received 10 g DC. The trial was double-blinded for the three lycopene groups and separately for the 2 DC groups; the trial lasted for 1 month. By the end of the trial there were dose-dependent changes in the gut microbiota profile in all three lycopene groups with an increase of relative abundance of, e.g., Bifidobacterium adolescentis and Bifidobacterium longum. This was also accompanied by dose-dependent changes in the blood, liver metabolism, skeletal muscle and skin parameters. Consumption of DC resulted in increased relative abundance of, e.g., Lactobacillus and a reduction of corneocyte exfoliation. This is the first study which reports the prebiotic potential of lycopene and DC.